Does the pursuit of outreach consistently stifle the financial performance of microfinance institutions in sub-Saharan Africa?. Issue 3 (2nd April 2020) - Chikalipah, Sydney
ABSTRACT: This article studies the relationship between outreach and the financial performance of 479 microfinance institutions (MFIs) in 37 countries of sub-Saharan Africa (SSA), covering the period 1998–2012. Findings indicate a positive and statistically significant relationship between outreach and the financial performance among MFIs in SSA. Providing small microcredits below the US$600 threshold is associated with lower profitability than larger loans, and MFIs serving more than 30, 000 clients reported a stronger financial performance than those serving fewer than 30, 000. The study findings have implications for managers and stakeholders in the microfinance industry of SSA.